2020
DOI: 10.1186/s12871-020-01172-x
|View full text |Cite|
|
Sign up to set email alerts
|

Landmark-guided versus modified ultrasound-assisted Paramedian techniques in combined spinal-epidural anesthesia for elderly patients with hip fractures: a randomized controlled trial

Abstract: Background Combined spinal-epidural (CSE) anesthesia is considerably challenging for elderly patients with hip fractures due to spine degeneration and limitations in positioning. This study aimed to investigate the ability of a modified preprocedural ultrasound-guided technique to improve the success rate and efficacy of CSE anesthesia for elderly patients with hip fractures. Methods This prospective, single-blinded, parallel-group randomized controlled trial included 80 patients (aged ≥65 years) who were sc… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

2
19
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 22 publications
(26 citation statements)
references
References 35 publications
2
19
1
Order By: Relevance
“…In a recent study, the first attempt success rate was 42.5% and 85% in landmark and US-guided preprocedural groups, respectively. [ 8 ] Nevertheless, in both the above-mentioned studies, patients with a difficult spinal anatomy were enroled, thereby the preprocedural US-assisted SAB resulted in better first attempt success rate as compared to our study. [ 7 8 ]…”
Section: Discussionmentioning
confidence: 67%
See 2 more Smart Citations
“…In a recent study, the first attempt success rate was 42.5% and 85% in landmark and US-guided preprocedural groups, respectively. [ 8 ] Nevertheless, in both the above-mentioned studies, patients with a difficult spinal anatomy were enroled, thereby the preprocedural US-assisted SAB resulted in better first attempt success rate as compared to our study. [ 7 8 ]…”
Section: Discussionmentioning
confidence: 67%
“…[ 8 ] Nevertheless, in both the above-mentioned studies, patients with a difficult spinal anatomy were enroled, thereby the preprocedural US-assisted SAB resulted in better first attempt success rate as compared to our study. [ 7 8 ]…”
Section: Discussionmentioning
confidence: 72%
See 1 more Smart Citation
“…Direct ultrasonographic visualization of the interspace has been successfully used to aid neuraxial anesthesia for the obese, elderly patients, or patients with abnormal anatomical surface landmarks. Ultrasonography enhances precision and efficacy for needle insertion [ 17 , 18 ], increases first-attempt success rates, and reduces needle insertion attempts. Point-of-care ultrasonographic guidance has limitations pertaining to equipment availability and provider experience [ 18 ].…”
Section: Discussionmentioning
confidence: 99%
“…Following publication of the original article [ 1 ], the authors reported two errors one in the Abstract section and one in the Result section.…”
mentioning
confidence: 99%